Pancreatic Cancer Gene Therapy Delivered by Nanoparticles. (April 2019) - Kurtanich, Trevin; Roos, Nicole; Wang, Guanmeng; Yang, Jesse; Wang, Alan; Chung, Eun Ji
Pancreatic cancer is one of the most lethal forms of cancer and has proven to be difficult to treat through conventional methods, including surgery and chemotherapy. Gene therapy serves as a potential novel treatment to interfere with genes that make this cancer so aggressive, but free nucleic acids have low cell uptake due to their negative charge and are unstable in circulation. Nanoparticles can serve as an effective carrier for a wide variety of gene therapies for pancreatic cancer as they can improve the circulation time, decrease the recognition by the immune system, and be functionalized to target specific surface proteins. In this review, we focus on therapeutic strategies using nanoparticles as carriers of small interfering RNA (siRNA), microRNA (miRNA), and gene augmentation (DNA) therapies in the context of pancreatic cancer. Lastly, we discuss the future outlook of nanoparticle-based therapies, including challenges in the clinical setting.